2018
DOI: 10.3390/mi9050215
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Laser-Based Rapid Prototyping of Micropumps

Abstract: The fabrication of microdevices for fluidic control often requires the use of flexible diaphragms in a way that requires cleanroom equipment and compromises performance. We use a CO2 laser to perform the standard ablative techniques of cutting and engraving materials, but we also apply a method that we call laser placement. This allows us to fabricate precisely-positioned and precisely-sized, isolated diaphragms. This in turn enables the rapid prototyping of integrated multilayer microfluidic devices to form c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…(B) PMMA micropump. Reproduced with permission from (Strike et al, 2018). (C) Cross section showing the laser (CO 2 ) cut microchannel.…”
Section: D Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…(B) PMMA micropump. Reproduced with permission from (Strike et al, 2018). (C) Cross section showing the laser (CO 2 ) cut microchannel.…”
Section: D Printingmentioning
confidence: 99%
“…(C) Cross section showing the laser (CO 2 ) cut microchannel. Reproduced with permission from (Strike et al, 2018). (D) 3D printed device made out of novel resin (Dowsil 732) that enables end-use devices.…”
Section: D Printingmentioning
confidence: 99%
“…Double-sided tape is the simplest form of an intermediate layer for bonding. It has been used to adhere PDMS to glass for micro particle image velocimetry (PIV) measurent devices [13], PDMS to PMMA for a microfluidic device for the observation of perturbation of Drosophila embryos [32], and PMMA to PMMA for droplet formation devices [33]. In our experiment, double-sided tape (3M Double Coated Tape 444, 3M Corp) was simply attached to the surface of a 3D-printed bottom part and the pneumatic port was cut out using a scalpel.…”
Section: Intermediate Layersmentioning
confidence: 99%
“…For the original research articles published in this special issue, polymers are shown to be functional in the most demanding of applications and also exceptionally useful for frugal engineering or rapid prototyping. We have three articles that focus on specific manufacturing improvements that aid in the fabrication of low-cost polymer microfluidics [3,4,5]. Song et al [3] demonstrate a new technique to bond two dissimilar thermoplastics, polycarbonate (PC) and polymethylmethacrylate (PMMA) via a PMMA solution dissolved in propylene glycol monomethyl ether acetate (PGMEA).…”
mentioning
confidence: 99%
“…The integration technique is relatively simple, has very low cost materials like commercial acrylic, tape and food wrap, and was demonstrated to be functional for a simple application of two-phase water in oil droplet generation, with a fabrication time of a few hours. Zhou et al [5] provides an alternative manufacturing technique for PMMA in microfluidics as high precision milling of a PMMA master mold is used, which can then be subsequently replicated to make polydimethylsiloxane microfluidic systems. Much smaller channels can be produced using a large milling tool when making a positive relief than if it was to mill out channels directly, and the roughness and minimum features were tested before and after PDMS replication to determine tolerances and fidelity.…”
mentioning
confidence: 99%